Peran Tokoh Agama Dalam Kriminal Remaja di Kota Pekalongan - Yusuf, Mochamad Aris; Putra, Robby Aditya (IAINU Kebumen, 2022)
The rise of the phenomenon of criminal acts committed by groups of teenagers in Pekalongan City. The condition is getting wild and out of control. The main causal factor is the aggressiveness of adolescents who highlight their identity and consider crime as their own existence, which is free and happy. Thus, the incident drew the attention of religious leaders to minimize criminal acts committed by teenagers now and in the future. The purpose of this research is to find out the role of religious leaders in minimizing juvenile crime in Pekalongan City. Researchers used a qualitative approach to the type of qualitative descriptive research. The results of this study are that religious leaders have given directions to adolescents in Pekalongan city to uphold the values ​​of the previous cleric ando train their respective abilities to acquire nationalistic and religious identity.